Impact of a community-based exercise programme on physical fitness in middle-aged and older patients with type 2 diabetes - Romeu Mendes; Nelson Sousa; José Themudo-Barata; Victor Reis (Elsevier, 2016)
Objectives: Physical fitness is related to all-cause mortality, quality of life and risk of falls in patients with type 2 diabetes. This study aimed to analyse the impact of a long-term community-based combined exercise program (aerobic + resistance + agility/balance + flexibility) developed with minimum and low-cost material resources on physical fitness in middle-aged and older patients with type 2 diabetes. Methods: This was a non-experimental pre-post evaluation study. Participants (N = 43; 62.92 ± 5.92 years old) were engaged in a community-based supervised exercise programme (consisting of combined aerobic, resistance, agility/balance and flexibility exercises; three sessions per week; 70 min per session) of 9 months' duration. Aerobic fitness (6-Minute Walk Test), muscle strength (30-Second Chair Stand Test), agility/balance (Timed Up and Go Test) and flexibility (Chair Sit and Reach Test) were assessed before (baseline) and after the exercise intervention. Results: Significant improvements in the performance of the 6-Minute Walk Test (Δ = 8.20%, p < 0.001), 30-Second Chair Stand Test (Δ = 28.84%, p < 0.001), Timed Up and Go Test (Δ = 14.31%, p < 0.001), and Chair Sit and Reach Test (Δ = 102.90%, p < 0.001) were identified between baseline and end-exercise intervention time points. Conclusions: A long-term community-based combined exercise programme, developed with low-cost exercise strategies, produced significant benefits in physical fitness in middle-aged and older patients with type 2 diabetes. This supervised group exercise programme significantly improved aerobic fitness, muscle strength, agility/balance and flexibility, assessed with field tests in community settings.